Negotiating Usability and Security in Digital Transformation: A Qualitative Study of Everyday Work in Finnish Vocational Education - Ojala, Anna-Liisa; Sipola, Tuomo; Saharinen, Karo (39th Bled eConference: Co-Creating Human-Centred and Responsible Digital Futures; Conference Proceedings, 2026)
This study examines how employees in Finnish vocational education institutions experience digitally mediated work and balance tensions between usability and digital security. Based on 25 qualitative interviews and complementary observations, the study shows that everyday work is shaped by fragmented digital environments, where multiple systems, changing interfaces, and external collaborations increase the complexity of work. The findings demonstrate that security measures, such as access restrictions and authentication practices, both enable and constrain work, often introducing friction into everyday tasks. In response, employees develop informal practices, including workarounds and the use of non-official systems, to maintain workflow. The findings show that employees continuously balance usability and security in fragmented multi-system environments shaped by changing digital systems and organisational boundaries. The study suggests that usability and security should be understood as continuously negotiated aspects of everyday digitally mediated work.